A highly efficient covalent organic framework film photocatalyst for selective solar fuel production from CO2. Issue 24 (28th April 2016) - Yadav, Rajesh K.; Kumar, Abhishek; Park, No-Joong; Kong, Ki-Jeong; Baeg, Jin-Ook
Abstract : The successful development of a triazine based covalent organic framework as an inexpensive and highly efficient visible light active flexible film photocatalyst for solar fuel production from CO2 is described. Abstract : Two-dimensional covalent organic frameworks (2D COFs) are a class of crystalline polymers with a design controllable platform that may be developed into a new type of metal-free photocatalyst. The exploration of new frameworks is, however, critical for further progress in this emerging field. To realize their full potential in practical light harvesting applications, the fabrication of a film type photocatalyst is equally essential. Here, we report the successful development of a triazine based covalent organic framework (2D CTF) as an inexpensive and highly efficient visible light active flexible film photocatalyst for solar fuel production from CO2 . For this research work, the condensation polymerization between cyanuric chloride and perylene diimide has been exploited for the first time as a new synthetic approach to the construction of 2D CTFs. The visible light-harvesting capacity, suitable band gap and highly ordered π electron channels contribute to the excellent performance of the film photocatalyst. The current study is a benchmark example of COF based photocatalysts for solar fuel production from CO2 and is expected to trigger further interest in potential solar energy conversion applications such as wearable devices.